2009
DOI: 10.1089/ten.tec.2008.0534
|View full text |Cite
|
Sign up to set email alerts
|

Buffered Platelet-Rich Plasma Enhances Mesenchymal Stem Cell Proliferation and Chondrogenic Differentiation

Abstract: The success of tissue engineering applications can potentially be dramatically improved with the addition of adjuncts that increase the proliferation and differentiation of progenitor or stem cells. Platelet-rich plasma (PRP) has recently emerged as a potential biologic tool to treat acute and chronic tendon disorders. The regenerative potential of PRP is based on the release of growth factors that occurs with platelet rupture. Its autologous nature gives it a significant advantage in tissue engineering applic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
267
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 362 publications
(292 citation statements)
references
References 29 publications
18
267
1
6
Order By: Relevance
“…34 In human mesenchymal stem cells, buffered PRP enhanced stem cell proliferation and induced the differentiation along the osteogenic and chondrogenic lineage as shown by the induction of the transcription factors Runx2 and Sox9 in monolayer cultures. 35 As shown here, in high-density pellet cultures, PRP induced the chondrogenic differentiation but not the development along the osteogenic or adipogenic lineage. Obviously, the cell culture or cell differentiation system (monolayer vs. 3D pellet culture) has to be taken into account when assessing the potential of putative chondrogenic inducers.…”
Section: Discussionmentioning
confidence: 50%
“…34 In human mesenchymal stem cells, buffered PRP enhanced stem cell proliferation and induced the differentiation along the osteogenic and chondrogenic lineage as shown by the induction of the transcription factors Runx2 and Sox9 in monolayer cultures. 35 As shown here, in high-density pellet cultures, PRP induced the chondrogenic differentiation but not the development along the osteogenic or adipogenic lineage. Obviously, the cell culture or cell differentiation system (monolayer vs. 3D pellet culture) has to be taken into account when assessing the potential of putative chondrogenic inducers.…”
Section: Discussionmentioning
confidence: 50%
“…Many studies have shown that PRP enhances proliferation and chondrogenic stem cell differentiation [35]. However, a limited number of in vivo studies have described the effect of PRP on the histologic appearance of the articular cartilage repair.…”
Section: Discussionmentioning
confidence: 99%
“…362 The in vitro literature indicates that this biological adjunct may increase chondrocyte proliferation as well as synthetic capability, while limiting the catabolic effects of an inflammatory joint environment. 10,233,287,418 In a rabbit model, the addition of PRP showed improved healing of OCDs treated with microfracture surgery. 284 Human studies have reported variable effects of PRP injections alone as well as in addition to surgery.…”
Section: Part IV -Alternative Treatmentmentioning
confidence: 97%